Analysis of Behaviorism Theory: Classical Conditioning and Operant Conditioning in Changing Students' Truancy Behavior - Dinda Putri Abadi; M. Ramli; Fitri Wahyuni; Dinda Putri Abadi; M. Ramli (Universitas Negeri Malang, 2025)
This article examines the application of Classical Conditioning and Operant Conditioning theories in behaviorism to modify students' truancy behavior at school. In the era of industrial revolution 4.0, students' active participation is essential to achieve optimal educational goals. Consistent student attendance will help them receive knowledge and form a strong character, while truant behavior will hinder academic and personal development. This research is a literature review that analyzes and summarizes relevant research and theories to gain an in-depth understanding of the topic. Classical Conditioning creates a positive relationship between class attendance and a pleasant experience. Operant Conditioning uses both positive and negative reinforcement, such as providing rewards for consistent attendance and consequences for non-attendance. The implementation of these two approaches in schools shows positive results, increasing attendance and reducing truancy. Thus, this theory provides practical solutions for educators to create an environment that supports positive behavior. This article is expected to provide insight into effective strategies in modifying student behavior.